2006
DOI: 10.1038/sj.jcbfm.9600310
|View full text |Cite
|
Sign up to set email alerts
|

Cholinesterase Inhibitor Blockade and its Prevention by Statins of Sympathetic α7-nAChR-Mediated Cerebral Nitrergic Neurogenic Vasodilation

Abstract: Cholinesterase inhibitors (ChEIs) have been used to treat Alzheimer's disease (AD). The efficacy of these drugs, however, is less than satisfactory. The possibility that ChEIs may have effects unrelated to ChE activity, such as negatively modulate neuronal nicotinic acetylcholine receptors (nAChRs) was evaluated. Since a7-nAChRs on cerebral perivascular sympathetic neurons mediate cerebral parasympathetic-nitrergic vasodilation, effects of physostigmine, neostigmine, and galantamine on a7-nAChR-mediated dilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 56 publications
2
34
0
Order By: Relevance
“…␣-BGTX, A␤s, and ␣-CTX IMI (a selective ␣ 7 -nAChR antagonist), however, failed to affect nicotine-induced nitrergic vasodilation in basilar arteries of the LYD pigs even when concentrations of these blockers were in the micromolar ranges, which is about 10-fold higher than the reported IC 50 value of ␣-CTX IMI in blocking ␣ 7 -nAChR-mediated inward currents (10). Furthermore, tropane and tropinone, which in high concentrations possess ␣7-nAChR agonistic activity (33,35), did not elicit vasorelaxation of isolated basilar arteries (Supplemental Fig. S3, A and B).…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…␣-BGTX, A␤s, and ␣-CTX IMI (a selective ␣ 7 -nAChR antagonist), however, failed to affect nicotine-induced nitrergic vasodilation in basilar arteries of the LYD pigs even when concentrations of these blockers were in the micromolar ranges, which is about 10-fold higher than the reported IC 50 value of ␣-CTX IMI in blocking ␣ 7 -nAChR-mediated inward currents (10). Furthermore, tropane and tropinone, which in high concentrations possess ␣7-nAChR agonistic activity (33,35), did not elicit vasorelaxation of isolated basilar arteries (Supplemental Fig. S3, A and B).…”
Section: Discussionmentioning
confidence: 59%
“…The bath solution, ND96, contained (in mM) 96 NaCl, 2 KCl, 1.0 MgCl 2, 1.8 CaCl2, and Two-electrode voltage clamp recording. A modified two-electrode voltage clamp recording was used in the present study (33). Two days after the injection of human ␣7, ␣3, and ␤2-subunit cRNAs, membrane currents of the oocytes were recorded in a chamber consisting of 1.3 ml cylindrical well at room temperature.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…SA, PA, and other saturated fatty acids with Ͻ20 hydrocarbon chains have been shown to potentiate ACh-induced, ␣7-nAChR-mediated inward currents, leading to facilitation of hippocampal neurotransmission (31). The postganglionic neurons/cell bodies of the rat SCG also are endowed with ␣7-nAChR (10,25,27). Whole-cell patch-clamp studies, however, demonstrated that PAME (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Nicotine (100 M), which binds ␣7-nAChR located on the rat SCG (26,27) to induce calcium influx into neurons (26,27) and generation of inward currents (10), superfused onto the SCG caused aortic relaxation with time course similar to that induced by FES of the SCG (Fig. 1H).…”
Section: Resultsmentioning
confidence: 99%